2016
DOI: 10.24953/turkjped.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of asthma education program on asthma control in children with uncontrolled asthma

Abstract: We aimed to evaluate the efficacy of a group education program on asthma control for children with uncontrolled asthma. Patients were randomized to receive 1-hour group education program with their parents or usual care. Our primary outcome was the change in asthma control test (ACT) between baseline and month 3 and secondary outcomes were health care utilizations and self report of exacerbations of asthma symptoms and missed school days. Change of ACT between baseline and 1st month and 3rd month was not signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 18 publications
(29 reference statements)
2
23
0
1
Order By: Relevance
“…Since the follow‐up assessment was at 5 months, seasonal variations could have attributed to changes in severity. There was no significant change in asthma control, results that are similar to other studies that showed no significant differences in clinical outcomes after educational intervention 20,21 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Since the follow‐up assessment was at 5 months, seasonal variations could have attributed to changes in severity. There was no significant change in asthma control, results that are similar to other studies that showed no significant differences in clinical outcomes after educational intervention 20,21 …”
Section: Discussionsupporting
confidence: 86%
“…Our study showed a significant improvement in parental knowledge and attitudes after the educational intervention; however, there were no differences in asthma severity and control. These results are comparable with other studies that showed improvement in knowledge, self‐efficacy, and attitudes after educational intervention; however, evidence regarding postintervention clinical outcomes has been conflicting 3,6‐9,16‐25 …”
Section: Discussionsupporting
confidence: 83%
“…Ten studies from interventions tailored to children and adolescents with asthma reported improved asthma control and decreased number of asthma exacerbations. One study found no changes in asthma control …”
Section: Resultsmentioning
confidence: 99%
“…Of the studies dealing with patient education interventions, 14/17 studies resulted in beneficial effects as measured by one or several health economic outcomes . Three studies found no health economic impact or effects of the interventions .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation